2019
DOI: 10.9734/afsj/2019/v13i130096
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Health Risk Assessment through Consumption of Baobab Leaf Cultivated in Katsina State, North West Nigeria

Abstract: Vegetables play important roles in human nutrition and health. They can also contain some undesirable components that can be harmful, e.g.  Pesticides and heavy metals. The objectives of the study were mainly to detect the presence of heavy metals (Cr, Cd, Fe, Ni, Mn, Pb and Zn) in sampled Baobab leaf in Katsina state Nigeria and assessed the human health risks associated with the consumption of the Baobab leaves. The content of these metals was assayed by the AAS method. The health risk to the local inhabitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
2
3
1
Order By: Relevance
“…Although a previous study from Katsina State, Nigeria [8] has reported the heavy metal Ni to be below detection level (BDL) in fish samples, with similar studies conducted in the state in legumes, cereals and vegetables corroborating the same finding [38][39][40][41][42][43]. The present study is among the few of such studies [44,13] that reported a detection of Ni in evaluated food samples.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Although a previous study from Katsina State, Nigeria [8] has reported the heavy metal Ni to be below detection level (BDL) in fish samples, with similar studies conducted in the state in legumes, cereals and vegetables corroborating the same finding [38][39][40][41][42][43]. The present study is among the few of such studies [44,13] that reported a detection of Ni in evaluated food samples.…”
Section: Resultssupporting
confidence: 84%
“…The risk assessment for carcinogenic exposure effect has revealed that the incremental lifetime cancer risk (ILCR) and the cumulative lifetime cancer risks (∑ILCR) were all above the safe limit for cancer in the children population with the heavy metal Ni contributing the highest risk and the sample of the fish sample of Clarias gariepinus having the highest cancer risk (Tables 6). [38][39][40][41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…From the Tables (2 and 3) the combined health risks for all the metals in the sample for the adults and children population represented as the HRI were below 1, an indication that the sample is safe for consumption. The current result is in agreement to what was previously reported in Katsina State [33][34][35][36][37][38][39].…”
Section: Non-cancer Riskssupporting
confidence: 93%
“…As seen from the results, the heavy metal Pb concentration that was above permissible limit of Pb in vegetables offers the suggestion that the sample is not safe for human consumption because of the high risk potential. In addition, the Pb and Mn mean values of the sample were higher than the reported mean values in studies that evaluate heavy metals in various food samples that were earlier conducted in Katsina State, Nigeria [33][34][35][36][37][38][39]. The apparent higher values obtained may not be unconnected with the illegal mining sites that are located within the vicinity of the sampling area.…”
Section: Heavy Metal Concentrations In Cultivated Cabbage Leavesmentioning
confidence: 63%
“…The observation that the heavy metals Pb and Fe have values that were higher than the regulatory bodies permissible limits is a pointer that the consumption of sample by the population is not safe because of the potentially high health risk. Also, the mean heavy metals concentrations of the sample was higher than the reported mean heavy metals concentrations in studies that evaluate heavy metals in various food samples that were earlier conducted in Katsina State, Nigeria [33][34][35][36][37][38][39]. The Apparent higher value obtained may not be unconnected with the illegal mining and metal artisanal sites that are located within the vicinity of the sampling area.…”
Section: Heavy Metal Concentrations In Cultivated Lettuce Leavesmentioning
confidence: 55%